Project SWORD-MMs: Science Words Optimization via Reading and Devised Mind Maps to Develop Student’s Metacognition - TOBILLA, JOAN (SEAMEO QITEP in Science, 2023)
The study aimed to determine the effect of PROJECT SWORD-MMs: Science Words Optimization via Reading and Devised Mind Maps to develop student’s metacognition. Specifically, it sought to answer the to what extent do student's manifest metacognition as they engage in PROJECT SWORD-MMs: Science Words Optimization via Reading and Devised Mind Maps. The study was conducted at Luis Aguado National High School in Trece Martires City, Cavite, Philippines. The study participants were 40 students under control group and 35 under experimental group, 75 from Grade 7, 8, 9 and 10. They were carefully chosen students based on the overall reading level -a joint and partnership effort with English teachers to determine the probable respondents and categorized as frustrated students. It has been a combination of qualitative research and quantitative research. Being a qualitative study, triangulation was done via interviews, and documentation of the students’ reflections and feedback about the compensatory interventions. As researchers, observation was done during the activity, and this was recorded in the Learner’s Progress Monitoring Report. All clarifications as to what the students are thinking and doing were recorded. In addition, some sessions were also recorded and accomplished the document analysis. Quantitative analysis was used to determine if there is a significant difference in the achievement level and metacognition of the students before and after engagement to Project SWORD-MMs as compensatory intervention. The present study has attempted to intensify collaboration and peer tutoring among science teachers to transform and develop the potential and skills of learners. The identified students under frustration level were promoted into instructional and independent level. They were able to develop their science vocabulary knowledge and improve their reading comprehension and metacognition. Moreover, critical thinking and creativity as well. Finally, these significant actions were able to withstand great foundations in promoting quality and inclusive science education among our learners. As the greatest mantra of the school, Excellence, Reaching Out, Sacrifices, no learners will be left behind. Nourishing the skills and potential of the learners would greatly contribute to transforming quality education and sustainable programs for them.